METODE GURU MENGAJAR ANAK AUTIS DALAM MENGGAMBAR DI SEKOLAH AUTISMA YPPA PADANG - Mutia Budhi Utami; Muzni Ramanto; Heldi . (Serupa The Journal of Art Education, 2012)
Abstract The purpose of this study is to describe how teacher’s methods  teach autistic children with autism in drawing. Data of this research are the primary data that is teachers' methods in teaching children with autism in drawing, and the secondary data is in the form of photographs and documentation. The source of  data in this research is oral sources as primary data that are teachers and literary study. Data were collected by using interview, observation and documentation technics in addition, instruments of this research are interview guide, recording equipment, observation sheets, and a camera. The finding of this research is teachers teach drawing to autistic children by using direct method, teacher give lesson to children with autism without explain first what activities that are going to be performed by children. To develop the children's potential a good or a correct method is need, to be used just like ABA (Applied Behaviour Analisis) method in teaching children with autism. Key words: teaching method, autistic children, drawing